Global prevalence of psittacosis in outbreaks: a systematic review and meta-analysis - Yu Sheng; Le-ying Jin; Ning Li; Yan Zhang; Ya-jun Shi (BMC Public Health)
Abstract Background Psittacosis is a globally underappreciated and frequently undiagnosed zoonotic disease, and it is often difficult to determine the number of individuals exposed to Chlamydia psittaci. Despite numerous reported cases and outbreaks worldwide, there has been no systematic assessment of psittacosis prevalence to date, which is crucial for evaluating the disease burden and developing vaccines. Our objective is to evaluate the global prevalence of psittacosis in outbreaks. Methods We conducted a comprehensive search across multiple databases, including PubMed, Web of Science, Cochrane Library, and Medline, from the date of establishment to May 15, 2024. Additionally, we manually searched reference lists of included articles and retrieved reviews to identify any supplementary articles. The primary summary data was the prevalence of psittacosis in the outbreaks. Pooled estimates of prevalence were calculated for both the entire population and subgroups using a random-effects model. Results Thirty-one eligible studies from 13 countries across four continents were included in this review. The pooled prevalence of psittacosis among 4,158 exposed individuals in outbreaks was 27.7% (95% CI: 20.9–34.9). Meta-regression analysis of six potential influencing factors (geographic region, outbreak sites, outbreak season, infectious source, publication year, and study quality) indicated that the source of heterogeneity may be associated with the outbreak sites (P = 0.031). Furthermore, among the cases collected, the hospitalization rate was 42.3% (95% CI: 24.7–60.8), the prevalence of pneumonia was 59.7% (95% CI: 41.4–76.9), and the fatality rate was 1.8% (95% CI: 0–6.9). Conclusions The global prevalence of psittacosis in outbreaks was found to be 27.7%, with a hospitalization rate of 42.3%, a pneumonia rate of 59.7%, and a mortality rate of 1.8%. Such knowledge will assist governmental and medical authorities in formulating public health policies for populations at high risk of bird exposure, assessing the disease burden, and developing effective vaccines.